Analisis Pengelolaan Arsip Terhadap Proses Temu Kembali Arsip di Dewan Perwakilan Rakyat Daerah Kabupaten Sidoarjo - M, Meirinawati; Alfarisy, Alfian Maulana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The background of this research is based on the importance of archive management in supporting the effectiveness of archival services, especially in archival reunion services. This study aims to analyze the management of archives on the process of reuniting archives in the Regional House of Representatives of Sidoarjo Regency. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. Data analysis was carried out using models from Miles and Huberman. The theory used refers to the theory put forward by Widjaja (2003) regarding the factors of good archives, including the use of the right storage system, qualified archival facilities, and qualified archival officers. The results of the study show that even though the Sidoarjo Regency Regional People's Representative Council has optimized the facilities and infrastructure of the archive center, there are still various obstacles, such as the limited number of archive employees, the lack of storage facilities (archive boxes and shelves), and the weak classification system which has an impact on the slow process of rediscovering archives. Therefore, it is necessary to increase the capacity of human resources, provide adequate facilities, and implement a more structured archive management system such as archive digitization so that the archive reunion process can run effectively and efficiently.